2009
DOI: 10.1242/jcs.047944
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy in mitosis of PtK1 cells is generated by random loss and nondisjunction of individual chromosomes

Abstract: Chromosome lagging at anaphase and migration of both sister chromatids to the same pole, i.e. nondisjunction, are two chromosome-segregation errors producing aneuploid cell progeny. Here, we developed an assay for the simultaneous detection of both chromosome-segregation errors in the marsupial PtK1 cell line by using multiplex fluorescence in situ hybridization with specific painting probes obtained by chromosome flow sorting. No differential susceptibility of the six PtK1 chromosomes to undergo nondisjunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Thus, chromosomes that lag in anaphase tend not to missegregate (i.e., cause nondisjunction) in human cells. These results are in agreement with data from nonhuman model cell systems showing that lagging chromosomes rarely missegregate (19,20).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, chromosomes that lag in anaphase tend not to missegregate (i.e., cause nondisjunction) in human cells. These results are in agreement with data from nonhuman model cell systems showing that lagging chromosomes rarely missegregate (19,20).…”
Section: Discussionsupporting
confidence: 91%
“…To determine whether lagging chromosomes lead to the uneven segregation phenotype, we analyzed chromosome segregation in mde4 Δ mutants expressing histone-mRFP using time-lapse analysis. We observed that 46% (30/65) of mde4 Δ cells that display lagging chromosomes in anaphase show uneven chromosome segregation in telophase, indicating that some but not all lagging chromosomes lead to segregation errors consistent with other studies [8–10]. However, because all cases (n=30) of uneven chromosome segregation appeared to be the result of earlier improper segregation of anaphase lagging chromosomes (for example see Movie S1), we combined the two classes (lagging (anaphase) and unevenly segregated (telophase) chromosomes) for subsequent analysis of fixed mde4 Δ and swi6 Δ cells.…”
Section: Resultssupporting
confidence: 91%
“…Through persistent chromosome shuffling, tumor cells with CIN continuously sample the genetic landscape with an almost limitless number of combinations, based on evidence in vertebrate cells that all chromosomes have an equal probability for mis-segregation [124]. Whereas some chromosome combinations may provide no selective advantage or a disadvantage, others could provide growth advantages to cells in the tumor microenvironment, particularly under the selective pressure applied by chemotherapy.…”
Section: Cin As a Target For Cancer Therapymentioning
confidence: 99%